2021
DOI: 10.1002/iub.2566
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of on‐pump versus off‐pump coronary artery bypass grafting surgery on serum cytokine and chemokine levels

Abstract: Coronary artery bypass grafting (CABG) surgery with two methods (on‐pump or off‐pump) can be used to rescue individuals with severe coronary artery disease (CAD). Each method might cause an inflammatory response, which can lead to some complications. The aim of this study was to compare the changes in serum concentrations of IFN‐γ, tumor necrosis factor (TNF)‐α, interleukin (IL)‐1α, IL‐1β, IL‐2, IL‐4, IL‐6, IL‐8, IL‐10, VEGF, MCP‐1, and epidermal growth factor between the two CABG surgery methods. Forty‐eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Several studies confirmed that the off-pump surgical revascularization technique omits the risk for inflammatory activation secondary to CBP administration [ 40 43 ]. In the Mirhafez et al [ 41 ] study serum cytokines levels in off-pump coronary surgery were lower compared with on-pump method. Despite some disadvantages, the off-pump technique still possesses a profound protective value in high-risk patients [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed that the off-pump surgical revascularization technique omits the risk for inflammatory activation secondary to CBP administration [ 40 43 ]. In the Mirhafez et al [ 41 ] study serum cytokines levels in off-pump coronary surgery were lower compared with on-pump method. Despite some disadvantages, the off-pump technique still possesses a profound protective value in high-risk patients [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mid-term survival and cardiovascular adverse event trends for on-pump CABG and off-pump CABG have been suggested to be comparable [ 12 , 13 ]. But on-pump CABG and off-pump CABG may differ in serum cytokine and chemokine levels and oxidative stress status, which may affect postoperative outcomes [ 14 , 15 ]. Therefore, this study differentiated the surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan bu çalışmada da, düşük ventilasyonun sonuçlar üzerinde bir etkisinin olmadığı görülmüş, buda bizim çalışmamızı destekler nitelikte olup, KPB cerrahisi geçirmiş hastalarda sitokinlerdeki değişikliklerin daha çok ekstrakorporeal dolaşım ekipmanlarından kaynaklandığını göstermektedir. Mirhafez ve arkadaşlarının 15 yaptığı çalışmada on-pump ve off-pump olarak gerçekleştirilen kardiyak cerrahi vakalarını serum sitokin seviyelerini karşılaştırmayı amaçlamışlardır. Çalışmalarında iki cerrahi yöntem arasında, IFN-γ, TNF-α, interlökin (IL)-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, VEGF, MCP-1 ve epidermal büyüme faktörünü karşılaştırmışlardır.…”
Section: Discussionunclassified
“…Cerrahi sonrası on-pump cerrahisi olan hastalarda IL-4, IL-6, IL-10, VEGF, IFN-γ ve MCP-1 serum seviyelerinde, off-pump cerrahisi olanlara kıyasla anlamlı bir artış olduğunu ve iki grup arasında anlamlı fark olduğunu belirtmişlerdir. Ayrıca KPB'ın sistemik inflamasyonu aktive edebileceğini, ancak her iki yönteminde bazı komplikasyonlara yol açabilen enflamatuvar yanıta neden olabileceğini belirtmişlerdir 15 . Yapılan bu çalışmada, sonuçları; çalışmamızdan farklı olarak kontrol grubu yerine ekstrakorporeal dolaşım sisteminin kullanılmadığı (offpump) kardiyak cerrahisi uygulanmış hasta grubu sonuçlarıyla karşılaştırmışlar ve benzer sonuçlar elde etmişlerdir.…”
Section: Discussionunclassified